Digital Capability Improvement Strategy of PT Telkomsel Employees (Regional Case Study of Papua and Maluku) - Sugiarto, Agus; Wahyuningtyas, Ratri (International Journal of Social Service and Research, 2023)
Telkomsel changed from a telecommunications company to digital telecommunications so that it can continue to stay in business and provide services to customers in accordance with current and future conditions. Telkomsel carried out a transformation covering various aspects starting from People, Process and Technology. In the process aspect, Telkomsel is now starting to form a new operational model that is designed based on customer centricity. Furthermore, on the technological aspect, Telkomsel has begun to carry out internal digitization through the use of technology that makes all processes possible quickly and efficiently. In the last aspect which is also one of the most important aspects is people. Telkomsel encourages its employees to adapt to the culture, ways of working and capabilities needed in the digital era. Telkomsel considers that employees' digital capabilities are important in responding to business changes. This research focuses on the People aspect, namely increasing employees' digital capabilities. This study aims to determine the digital capability readiness of Telkomsel employees in facing the company's digital transformation, find out the right strategy to meet capability needs and improve employee digital capabilities. The data collection method was carried out through observation, surveys and interviews with 130 employees in the Papua and Maluku regional Telkomsel. Based on the results of data processing, it was found that there were 130 survey data for position bands I, II, III and IV, as well as 10 interview data for position bands III and IV. Based on the research results from the two stages of analysis, namely descriptive analysis of digital culture variables and digital attitude variables. With the results of the observations that have been made, namely employees have potential capabilities that support the transformation process to face industry 4.0 opportunities. PT. Telkomsel in the Papua and Maluku Regions needs improvement towards digital attitudes, with a strategy of fulfilling and increasing digital capabilities to be able to support digital transformation, namely: 1) Maximizing programs from the company for the development of employee digital culture and skills. 2) Creating cultural and digital skills development activities for employees.